Newborn Screening for Mucopolysaccharidosis Type II in Illinois: An Update - Barbara K. Burton; Rachel Hickey; Lauren Hitchins (MDPI AG, 2020)
Mucopolysaccharidosis type II (MPS II, Hunter syndrome) is a rare, progressive multisystemic lysosomal storage disorder with significant morbidity and premature mortality. Infants with MPS II develop signs and symptoms of the disorder in the early years of life, yet diagnostic delays are very common. Enzyme replacement therapy is an effective treatment option. It has been shown to prolong survival and improve or stabilize many somatic manifestations of the disorder. Our initial experience with newborn screening in 162,000 infants was previously reported. Here, we update that experience with the findings in 339,269 infants. Measurement of iduronate-2-sulfatase (I2S) activity was performed on dried blood spot samples submitted for other newborn screening disorders. A positive screen was defined as I2S activity less than or equal to 10% of the daily median. In this series, 28 infants had a positive screening test result, and four other infants had a borderline result. Three positive diagnoses of MPS II were established, and 25 were diagnosed as having I2S pseudodeficiency. The natural history and the clinical features of MPS II make it an ideal target for newborn screening. Newborn screening was effective in identifying affected infants in our population with an acceptable rate of false positive results.